Using turf transplants to reintroduce native forest understory plants into smelter‐disturbed forests. Issue 3 (19th December 2015) - Santala, Kierann R.; Monet, Stephen; McCaffrey, Tina; Campbell, Daniel; Beckett, Peter; Ryser, Peter
Abstract : This study investigated factors affecting transplantation success of native forest understory vegetation on metal‐contaminated soils. One year after transplantation along a gradient of historical Cu–Ni smelter pollution in Sudbury, Canada, community‐level characteristics of the transplanted plots and short‐term indicators expressing the performance of selected species were assessed. Thirty 16‐m 2 plots were studied, each established with 45 transplanted 0.56 × 0.64−m turfs 10 cm thick, extracted from mixed‐hardwood forests slated for development. Species richness, diversity, and evenness were not affected by environmental conditions but short‐term responses of root growth and sexual reproduction of selected species to environmental variables indicate a need for long‐term monitoring. Root growth of Clintonia borealis (Aiton) Raf. and Gaultheria procumbens L. was positively related to soil temperature. Root growth of G. procumbens correlated negatively with soil Ni availability, but in all plots, root growth was comparable with the literature values from unaffected forests. Flowering frequency of G. procumbens correlated negatively with soil pH and positively with tree cover, corresponding to ecological requirements of this species. Soil SO 4 − 2 had a negative effect on sexual reproduction of C. borealis . Unexpectedly, fruiting of C. borealis responded positively to Ni, and fruiting of Maianthemum canadense Desf. positively to As, possibly due to interdependencies among soil variables. The results are encouraging with respect to transplant success, as effects of smelter‐related variables were relatively minor, but species‐specific responses of the selected species to environmental factors indicate that species performance is dependent on site‐specific conditions, potentially influencing long‐term success of the transplants.